Etika Digital dalam Menanggulangi Ujaran Kebencian pada Penggunaan Media Sosial Instagram oleh Generasi “Z” - Dini Naila Utami; Asep Deni Normansyah; Darda Abdullah Sjam (UNIVERSITAS SERAMBI MEKKAH, 2024)
One of the social media that is often used lately especially for Generation-Z is Instagram. With the number of Instagram social media users in Indonesia reaching more than 104.8 million users. The Instagram social media users are young people. So that makes Instagram a social media that provides freedom in the use of content. The freedom in using social media instagram often does not pay attention to ethics and morals in social media so that it becomes a concern. The purpose of the research intends that Generation-Z is able to have an awareness of the importance of digital ethics on social media, can increase awareness in interacting on social media wisely, and can also analyze the negative impact in the use of social media on Instagram. The research method involves interviews, observations, and documentation with interviews with the principal, teachers, and also students totaling 6 people. The results of the study are that Generation-Z has an understanding of digital ethics in using social media, where digital ethics become manners and manners in using Instagram social media, the actions they take in responding to netizens on Instagram social media by responding to positive comments, as well as strategies in overcoming the existence of hate speech to Generation-Z by providing habituation before learning fostered by subject teachers, socialization on school social media accounts, BK or on the osis social media account.